Targeting the Hsp90 C-terminal domain by the chemically accessible dihydropyrimidinone scaffold1. Issue 18 (4th March 2015) - Strocchia, Maria; Terracciano, Stefania; Chini, Maria G.; Vassallo, Antonio; Vaccaro, Maria C.; Dal Piaz, Fabrizio; Leone, Antonietta; Riccio, Raffaele; Bruno, Ines; Bifulco, Giuseppe
<x xml:space="preserve">Abstract</x> Identification of a first DHPM-based lead compound useful for developing a new class of Hsp90 C-terminal inhibitors for cancer therapy.